Smartboard for student information systems using gamification framework - Bening Insaniyah Al-Abdillah; Gunawan Wang (Sean Institute, 2024)
This study aims to analyze the application of gamification through the user experience of a gamification-based student information center system by providing functions of mini-games, event information, news, service center, and take your wefie. The MDA (Mechanical, Dynamic, Aesthetic) method is used to describe the mechanical, dynamic, and aesthetic aspects of the system. In this study uses questionnaire to evaluate the system. The results of this study are expected to provide insight into how users interact with the student information center system and how the user engagement, motivation, and literacy can be improved by optimizing mechanics, dynamics, and aesthetic aspects. This research has the potential to contribute to the development of a student information center system that is more responsive to the needs and preferences of users, especially students, with the aim of increasing student engagement and active interaction in a digital campus environment.